Power Relation and Cooperation between Actors: Issue of Nickel Mining Business Licenses in Konawe Regency - Andi Muh Dzul Fadli; Oekan S Abdoellah; Agustinus Widanarto; Muradi Muradi (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
Natural resource management (SDA) such as nickel has become a logical choice for local governments to achieve results for regional development achievement. This is because nickel is one of the trade and business commodities between countries. However, a permit is required for the management of these natural resources. Meanwhile, the government cannot be separated from the cooperation between actors in the context of social situations regarding decisions about issuing permits for mining companies (IUP). Therefore, this paper aims to interpret the context of the social situation in nickel mining permit decision-making. In this paper, the data were obtained based on interviews with 26 informants, observations, and a review of documents. The study's results, in a review of the theory of manifestation of power relations, show that there is cooperation among regional heads, businesses, brokers, and village government officials. On the other hand, in the examination of the three-dimensional theory of power, the context of the social situation is that there is no latent conflict between the actors. The finding in this paper is the neglect of the role of local NGOs in the nickel IUD issuance process, particularly in defending the interests of local communities in the pre-mining phase.